PENGARUH ASPEK PENDIDIKAN, NORMATIF, DAN MEDIA SOSIAL TERHADAP KONTROL EMOSI SISWA MADRASAH ALIYAH DI ACEH - Yuni Setia Ningsih (Jurnal Ilmiah Didaktika, 2019)
Teenage students have unpredictable emotional tendency. The unbalance of students' anger and sadness can be influenced by certain factors. In controlling the emotions, such as anger and sadness, the students of Islamic Senior High School have different ways.  It is wondered that they will vent those emotions towards things that are not in accordance with religious teachings. In this regard, this research was done to know the influence of educational, normative (religious law) and also social media (internet) aspects on their emotions. Therefore, this paper is a result of a qualitative study which is aimed at finding the dominant factors causing anger and sadness, and the level of controlling ability of the emotions. The instrument used was a questionnaire with pedagogical (educational), normative, and social media approaches. Findings show that the dominant factor causing anger is that someone they respect is not being respected.  On the other hand, the dominant factor causing sadness is the one they cared about were in the state of sorrow. Furthermore, the level of anger controlling ability is in very good category, with an average value of 21.13103 (range 0-30). In addition, the level of sad controlling ability is in very good category too, with an average value of 20.72414 (range 0-30).